If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5z + 5 = 2(8z + -3) Reorder the terms: 5 + 5z = 2(8z + -3) Reorder the terms: 5 + 5z = 2(-3 + 8z) 5 + 5z = (-3 * 2 + 8z * 2) 5 + 5z = (-6 + 16z) Solving 5 + 5z = -6 + 16z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-16z' to each side of the equation. 5 + 5z + -16z = -6 + 16z + -16z Combine like terms: 5z + -16z = -11z 5 + -11z = -6 + 16z + -16z Combine like terms: 16z + -16z = 0 5 + -11z = -6 + 0 5 + -11z = -6 Add '-5' to each side of the equation. 5 + -5 + -11z = -6 + -5 Combine like terms: 5 + -5 = 0 0 + -11z = -6 + -5 -11z = -6 + -5 Combine like terms: -6 + -5 = -11 -11z = -11 Divide each side by '-11'. z = 1 Simplifying z = 1
| 22-3x=4x | | 4y-4=7(y-1) | | x(x-0.05)=300 | | -10+4w+6=-2w+23-3w | | 1b+2=-3b | | -10+4w+6=-23-3w | | 12/8x=7/10 | | 7a-4=4a+19 | | 9x^4-8x^2= | | 3x-11/4=-2x | | 3(5b-2)+2=26 | | 8a+3a+18=8+7a+6 | | 4=5/w-2 | | -1/9x=-3/4 | | -1=-3z+20 | | [x-3]=4x+9 | | 3(y-8)-2y=12 | | -9=r+(-2) | | 5.2/4.4 | | -4(d+12)=16 | | [-5x]=35 | | -18=3X-3 | | -29=15+y | | 6x+6(-3)=-8 | | 10q-9q=4 | | -j=-103 | | 2(3x+4)+x= | | 2-c=3 | | [-5x]=10 | | 9(2y+5)-2y-8= | | 5x^3-32x^2-21x=0 | | 8.8=x+x |